Social History of Islamic Education During the Caliphate of Ali Ibn Abi Thalib (656-661M) - Attamimi, Taufik Abdullah; Della, Dhia Alfa; Khairunnisa, Ririn; Hasanah, Uswatun (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This research discusses the reign of Caliph Ali bin Abi Talib who experienced a lot of upheaval, opposition and chaos of Medina Muslims. The beginning of Islamic rule of Islamic education was centered in Medina. After the death of the Prophet Muhammad, Islamic power was led by Khulafa Ar-Rashiddin and very rapid development, such as the expansion of the territory of Islamic power extended to Egypt, Persia, Syria, and Iraq. besides being concerned with Islamic power they also paid more attention to the education sector in the period after the death of the apostle for the sake of religious syi'ar and making the Islamic State stronger. This research uses a quantitative approach with a library research method by collecting, processing and analyzing data from relevant literature and references sources. The results showed that the social conditions during the reign of Caliph Ali bin Abi Talib were very much upheaval, opposition and chaos of Medina Muslims, the life history of Caliph Ali bin Abi Talib from birth to death, educational institutions, stratification, teacher and student interaction and learning methods used, learning media, to learning evaluation during the time of Caliph Ali bin Abi Talib.